Analysis of the Behavioral Aspects of Project Planning and Budgeting at CV Karya Jaya in Surabaya - Damayanti, Fitri; Trisnaningsih, Sri (Journal of World Science, 2023)
The success of a budget plan lies in the behavior of the manager or head of the company. CV Karya Jaya is an expansion of a business engaged in construction, such as repairing plumbing (PDAM partners), paving roads, and other construction matters, so that for the aspect of budgeting with capital that is already owned from the profits of several types of ongoing businesses. This study aims to analyze behavioral factors in project planning and budgeting. In addition to knowing the role of budgeting that impacts the behavior of leaders to make decisions and commitments, to increase customer satisfaction, job certainty for employees, and have a good image of partner companies. This study uses a descriptive qualitative method. Sources of data that have been obtained from this study are primary data and secondary data. Civil project services on maintenance in Putat Surabaya get a loss of IDR 1,034,000 because the total amount of the project is IDR 150,649,000. Civil pump house repair project services for three months of work in Surabaya. In the civil construction of the pump house, it suffered a loss of IDR 156,870,900. The Blower Ngagel I civil project experienced a profit of IDR 11,623,500, but payments from vendors for six months will be paid in December 2022. All the work was carried out correctly and according to the completion target, but several projects experienced losses due to improper budget planning.